Application of high-frequency ultrasound to assess facial skin thickness in association with gender, age, and BMI in healthy adults - Ying Meng; Lan Feng; Jiali Shan; Zixu Yuan; Lin Jin (BMC Medical Imaging, 2022)
Abstract Background and objective High-frequency ultrasound plays an extremely important role in normal skin measurement, skin disease diagnosis, and aesthetic medicine. This study aimed to estimate the epidermal and dermal thicknesses at eight different facial sites in healthy adults using high-frequency ultrasound, and to evaluate the correlation of epidermal and dermal thicknesses with age and body mass index (BMI). Methods Facial skin assessment was performed on 118 participants using high-frequency ultrasound. The epidermal and dermal thicknesses of forehead, glabella, temple, eyelid, nasal dorsum, zygoma, submandibular, and neck were measured. The correlation of the epidermal and dermal thicknesses with age and BMI was analyzed by the linear correlation analysis. Results The epidermal and dermal thicknesses in men were significantly higher than those in women (P < 0.05), except for the thicknesses of zygomatic epidermis and neck dermis. The dermal thickness on zygoma and submandibular in young women was significantly higher than in middle age and old women (P < 0.05). Overall, with the increase of age, the thickness of facial skin decreased in women, mainly in the forehead, glabella, zygoma, and submandibular. In women, the epidermal and dermal thicknesses of neck were correlated with BMI (r = 0.392, 0.241, P < 0.05, respectively). However, in men, the epidermal and dermal thicknesses were correlated with age only in zygoma dermis (r = − 0.327, P < 0.05), while there was no correlation between the epidermal and dermal thicknesses and BMI. Conclusion Gender, age, and BMI had significant effects on the epidermal and dermal thicknesses at different facial sites.